Ready-to-assemble (RTA) housing system as self build housing in Malaysia / Wan Srihani Wan Mohamed - Wan Srihani, Wan Mohamed (2015)
The issue of inadequate housing for the poor has been a pressing issue confronting most developing countries. The problem of land acquisition, access to housing finance, high building standards and the limited government action to alleviate the housing shortages, has resulted in many policy changes and implementation from time to time depending on situations. In an attempt to address such housing problems in rural area, a study was conducted on an alternative approach. The primary aim of the research is to examine pragmatic solutions to the problems through self build housing. The research program is divided into two parts, in which the first part is to gauge the acceptance level on self build housing concept among lowincome households. Its first objective is to identify the extent of recognition and establish issues on the concept of self build houses. Secondly, it is important to ascertain the knowledge and skills in housing construction. Thirdly, the study needs to establish factors of housing demands which can affect the types of housing provided in a certain area. The first analysis concluded that self build housing is still relevant in Malaysian context. It is critical for the younger families to be able to own a house and nearly 50% of the respondents could only afford a house that is below RM30, 000. Hence, the invention of a simplified system that encourages self build housing program to reduce labour cost is necessary. The second part of the research program formulated a prototype adaptingSegal self build principles with considerations to local context. The principles were adapted iv closely to meet the low-technology criteria for self build housing particularly in Malaysia. A village was chosen to test the prototype referred to as RTA or Ready-To- Assemble Self Build Housing System to ascertain willingness of participating in self build activity using a simplified construction. The prototype was assembled using illustrated manual as their guideline. A total of 33 participants were involved during that four-day program. The questionnaire opts for Likert-type scale with open-ended questions as the tool in this research. The findings from the second part of the research revealed that the success of self build housing mainly depends on the willingness of the communities involved to participate in the project. However, through a simplified construction system, it strongly supports the self build concept as an alternative housing supply in the rural area, making the communities more positive towards building houses together. Self build housing sector has the potential of being the third sector in housing development. Conclusions have led to possibilities of developing this sector to address the problem of affordable quality housing for the lower income groups. Nevertheless, to make the contribution of this sector significant, participation from local authorities, establishment of rural studio consultations and involvement of researchers is essential as it gives empowerment through community planning.